Comprehensive life cycle assessment of the corn wet milling industry in the United States - Taylor, Caroline; Maroccia, Justin; Masterson, Margaret; Rosentrater, Kurt A. (Frontiers in Energy Research, 2023)
High fructose corn syrup (HFCS) 55 (HFCS55) is a sweetener made from corn composed of 55% fructose and a mix of glucose and minor amounts of short chain oligosaccharides that is used in a range of food applications as a sweetener, preservative, flavor enhancer, moisture retainer, and to provide texture. Understanding the potential environmental or sustainability benefits of HFCS55 can assist the corn wet milling industry in identifying targets for advancement, research, and potentially mitigation. The objective of this study was to assess the cradle-to-gate environmental impacts of U.S. average production of HFCS55, based on confidential data supplied by 13 participating facilities. The life cycle impact potential of the sweetener was estimated using the Tool for the Reduction and Assessment of Chemical and Environmental Impacts (TRACI 2.1). Additional impact categories were including for land use (ReCiPe 2016 midpoint H), Global Warming Potential (100 year), and Cumulative Energy Demand. Environmental hotspots identified in the production of HFCS55 indicated that direct emissions from the conversion process contribute over 50% of the global warming potential, as well as the overwhelming bulk of energy and fuels used in the system, and 35-40% of acidification and ecotoxicity impact potentials and the potential respiratory effects caused by particulate matter. Coal and natural gas extraction and combustion accounted for 70-90% of the global warming impacts for process heat and power, and their extraction also contribute significantly to acidification and ecotoxicity. About 40% of the global warming potential for HFCS55 was generated by fuel used in processing for the aggregated industry average HFCS55. Nearly half of the HFCS55 produced was in facilities that utilize coal in cogeneration of steam and electricity, and that grouping had almost 20% higher impact than the aggregated. Replacing coal in the industry average with natural gas could lower impact about 20%; for the coal-using cogeneration group. Replacing all coal and natural gas with biogas from process residues potentially could more than halve the global warming potential depending on which grouping a facility was in, although this scenario needs further evaluation. Heat and electricity had the largest environmental impacts.